Changes in yellow bristle grass (Setaria pumila) incidence in Waikato dairy pastures over 4 years - Tozer, K.N.; Cameron, C.A.; James, T.K. (New Zealand Plant Protection, 2012)
Thirtynine Waikato dairy pastures have been surveyed annually each February for 5 years to quantify changes in cover of yellow bristle grass and to determine if management factors influence this After a severe drought yellow bristle grass ground cover increased from 4 to 11 (2008 to 2009) and has since remained at this level Ryegrass cover declined after the drought and has not returned to predrought levels while clover cover has increased There was a much higher than average 2011/2012 summer rainfall possibly causing the reduced summer grass and broadleaf weed cover measured in February 2012 By the end of the survey period there was no reduction of yellow bristle grass cover from any of the following farm practices aimed to improve pasture performance summer cropping undersowing oversowing and nonselective herbicide applied during summer